MicroRNA expression profile in bovine mammary gland parenchyma infected by coagulase-positive or coagulase-negative staphylococci - Bagnicka, Emilia (Vet Res, 2021)
MicroRNAs (miRNAs) are short, non-coding RNAs, 21–23 nucleotides in length which are known to regulate biological processes that greatly impact immune system activity. The aim of the study was to compare the miRNA expression in non-infected (H) mammary gland parenchyma samples with that of glands infected with coagulase-positive staphylococci (CoPS) or coagulase-negative staphylococci (CoNS) using next-generation sequencing. The miRNA profile of the parenchyma was found to change during mastitis, with its profile depending on the type of pathogen. Comparing the CoPS and H groups, 256 known and 260 potentially new miRNAs were identified, including 32 that were differentially expressed (p ≤ 0.05), of which 27 were upregulated and 5 downregulated. Comparing the CoNS and H groups, 242 known and 171 new unique miRNAs were identified: 10 were upregulated (p ≤ 0.05), and 2 downregulated (p ≤ 0.05). In addition, comparing CoPS with H and CoNS with H, 5 Kyoto Encyclopedia of Genes and Genomes pathways were identified; in both comparisons, differentially-expressed miRNAs were associated with the bacterial invasion of epithelial cells and focal adhesion pathways. Four gene ontology terms were identified in each comparison, with 2 being common to both immune system processes and signal transduction. Our results indicate that miRNAs, especially miR-99 and miR-182, play an essential role in the epigenetic regulation of a range of cellular processes, including immunological systems bacterial growth in dendritic cells and disease pathogenesis (miR-99), DNA repair and tumor progression (miR-182). SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13567-021-00912-2.